Правова природа відповідальності учасників акціонерних правовідносин - Сядриста, І. І.; Siadrysta, I. I.; ORCID: http://orcid.org/0000-0002-4340-3593 (Європейські перспективи. - 2019. - № 1. – С. 132-138, 2019)
Розглянуто правову природу відповідальності учасників акціонерних правових зв’язків та її співвідношення із загально-цивілістичним розумінням юридичної відповідальності. Зазначено, що внутрішні корпоративні правовідносини є підгалуззю цивільного права, а їх підвид – акціонерні, відповідно, інститутом останнього, оскільки до предмету корпоративного права входять внутрішні корпоративні правовідносини, що мають майново-організаційний характер та виникають між учасниками корпоративних правовідносин стосовно реалізації їх корпоративних прав та виконанні обов’язків.

The scientifi c article considers the legal nature of the responsibility of participants in Joint-Stock relations and its relationships with the general civil understanding of legal responsibility. In the formation of corporate law, there is a mutually agreed action of the rules of private and public law, because the creation and functioning of business societies covers the relations of ownership, entrepreneurship, and competition in the securities market, so they all interact in one way or another with corporate legal relations, as well as the process of insolvency (bankruptcy), depository activities, taxation, privatization, investment obligations etc. Based on the analysis, it was concluded that internal corporate legal relations are a sub-branch of civil law, and their subspecies are Joint-Stock legal relations, respectively, they are the institution of the latter, since corporate law regulation include internal corporate legal relations, which have property-organizational nature and arising between participants of corporate legal relations at implementation of their corporate rights and duties. Despite the fact that participants of joint legal relations may be subject to different types of responsibility in certain legal relations, and the use of one type does not exclude the possibility of using the other one, shareholder responsibility has private (civil) nature, since the last one arises as a result of causing harm to participants of joint legal relations, which are the subjects of private law and which relations are regulated at the local level.All other types of liability that may apply to participants in a joint legal relationship cannot significantly affect the legal status of persons as participants in intra-corporate legal relations. Civil legislation defi nes only general provisions on the liability of participants in Joint-Stock relations, and therefore, it has all properties of the latter as a kind of civil liability. However, the features of the legal nature of the corresponding legal relations, which ensure the balance of interests of the Joint-Stock Company and its shareholders, require special regulation and determination of the specifi cs of the responsibility of the respective subjects. The essence of these relations and certain legitimate relations between their subjects (in a Joint-Stock Company, the corporate interest of each shareholder is realized through the direct implementation of the rights defi ned by the legislation and intra-corporate acts of the company, including the right to protection (regulatory element), and indirectly through the activities of management of the society (organizational element) entails the impossibility to squeeze them into the existing approaches that have developed regarding the varieties of civil legal relationship.

Рассмотрено правовую природу ответственности участников акционерных правоотношений и ее соотношение с общегражданским пониманием юридической ответственности. Подчеркнуто, что внутренние корпоративные правоотношения являются подотраслью гражданского права, а их подвид – акционерные, соответственно, институтом последнего, поскольку в предмет регулирования корпоративного права входят внутренние корпоративные правоотношения, носящие имущественно-организационный характер и возникающие между участниками корпоративных правоотношений при реализации их корпоративных прав и исполнении обязанностей.
Сядриста, І. І. Правова природа відповідальності учасників акціонерних правовідносин / Сядриста Ірина Ігорівна // Європейські перспективи. - 2019. - № 1. – С. 132-138.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; акціонерне товариство; joint stock company; акционерное общество; акціонерні правовідносини; shareholder legal relations; акционерные правоотношения; відповідальність; responsibility; ответственность; корпоративні правовідносини; corporate legal relations; корпоративные правоотношения